Enhanced pulse amplitude estimation for electronic warfare systems - Lee, Yu-Ri; Kim, Dong-Gyu; Kim, Hyoung-Nam (IET radar, sonar & navigation, 2019)
In electronic warfare systems, the pulse amplitude (PA) of the received signals, which are emitted by enemies, has been used as one of the essential quantities for separating the mixed source signals. The PA is affected by time of arrival (TOA) and time of departure (TOD) estimation performance. Among methods of estimating TOA and TOD, there is a method of processing a signal in sample units in the time domain. This method has a disadvantage that it is completely affected by noise. This disadvantage can be overcome by using denoising techniques as in previous studies. However, conventional studies applying denoising are limited to the subject of signal detection, and there is no discussion on the problem of PA estimation due to the TOA and TOD estimation errors that occur after denoising. Therefore, we propose a power estimation-based PA estimation method using shrinked PW to be robust for TOA and TOD errors in sample units after wavelet packet denoising with high-order statistics. Simulation results show that the proposed PA estimation method has a smaller error at the same SNR when an unmodulated signal is received. Moreover, the proposed method can provide good performance even when a frequency modulated signal is received.